Fatty acids composition of seed oils obtained from eight Iranian pomegranate cultivars - Nafiseh Momeni; Hossein Ali Asadi-Gharneh (Institue of Medicinal Plants, ACECR, 2021)
Background: The pomegranate (Punica granatum L.) is one of the oldest edible fruits that belongs to the Punicaceae family and different parts of it have been used as medicinal plant. The pomegranate seeds are the sources of lipid, sugars, protein and essential minerals. Objective: This study was planned to investigate the composition of fatty acids in seed oil of eight Iranian pomegranate cultivars. Methods: Mature ripe fruits of eight pomegranate cultivars were harvested from a commercial pomegranate orchard. Arils were dried via an air oven and oil extraction process was performed using Soxhlet apparatus with petroleum ether as solvent. Finally, identification of fatty acids in pomegranate seed oil was done by gas chromatography (GC). Results: A considerable variation was observed in the composition of fatty acids and oil content of pomegranate cultivars. The total oil content of the Iranian pomegranate cultivars was ranged from 10.81 g/100 g DW to 15.03 g/100 g DW palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1), linoleic acid (C18:2) and linolenic acid (C18:3) were major fatty acids in the Iranian pomegranate cultivars. Linolenic acid being considered and identified as the main fatty acid, ranged from 71.35 % for Poost-Ghermez to 74.58 % for Gar cultivars (P < 0.05). In saturated fatty acids, palmitic acid (C16:0) with a mean of 0.414 (g/100 g DW) and in unsaturated fatty acids, linolenic acid (C18:3) with a mean of 7.3 (g/100 g DW) were the dominant fatty acids found in studied pomegranates. Also, our results showed that Sorahi cultivar had the highest oil content (15.03 %), C18:1 (8.92 %) and C20:1 (1.12 %) among selected pomegranate cultivars. In pomegranate seed oil, 7.84 % of the fatty acid was saturated and 91.08 % was unsaturated. In addition, the ratio of polyunsaturated fatty acids to saturated ones were found 9.83 to 11.54. Conclusion: Eight cultivars of the Iranian pomegranate seed oils in this study contained very high levels of unsaturated fatty acids especially in linolenic acid. The quality obtained due to fatty acid composition can in turn enhance the general condition of the heath.